Evaluation of Staphylococcus aureus resistance profile isolated from nursing students in an institution of higher education - Carolina Marino; Juliana Tramontini Marcatto; Carolina Yumi Gushiken; Rodrigo Santos Lima; Daniela Vanessa Moris; Marcus Vinicius Pimenta Rodrigues (Universidade Estadual de Maringá, 2016)
Staphylococcus aureus causes a large variety of infections, where many of them are acquired in the hospital environment. A significant part of the population is a nasal carrier of this type of microorganism. The present study evaluated the nasal colonization by S. aureus, identifying its resistance profile in nursing students from a private educational institute of higher education. Nasal swab samples were collected and identified for S. aureus. Moreover, an antibiogram assay was performed, followed by the search for ermA and ermC genes using PCR. Sixty-two students were included and we isolated 20 positive samples (32,5%) for S. aureus. For the phenotypic profile, 30% were found to be resistant to Erythromycin and 10% to Oxacillin and Cefoxitin. For the D-test in the genotypic profile, 25% presented mecA gene (MRSA), 5% of ermA gene, 35% of ermC gene and 10% with ermC and mecA genes. These data reinforce the necessity of monitoring bacterial colonization in hospital environment, which are potentially resistant in health professionals.